SUSTAINABLE FINANCIAL MANAGEMENT: A CRITICAL ANALYSIS OF CURRENT RESEARCH AND FUTURE PROSPECTS - Loso Judijanto; Ari Purwanti; Al-Amin (CV. Adiba Aisha Amira, 2024)
Sustainable Financial Management has emerged as an important paradigm in the modern financial world, reflecting the urgent need to integrate environmental, social, and governance (ESG) considerations into financial practices. The study in this research uses the literature research method. The results show that; 1) The integration of ESG factors in financial decisions shows the potential to improve long-term financial performance and reduce risks. 2) Key challenges include the lack of standardisation in ESG metrics, data limitations, and gaps in understanding among practitioners. 3) Technological advances, especially in data analytics and artificial intelligence, open up new opportunities for more effective analysis and implementation. 4) Global regulatory trends are leading to an increased need for sustainable finance practices. With that, sustainable financial management offers significant opportunities to create long-term value while contributing to global sustainability goals.